The past is prologue: criminal specialization continuity in the delinquent career - DeLisi, Matt (Youth violence and juvenile justice, 2019)
The versatility/specialization debate in criminology has important theoretical, research, and juvenile/criminal justice ramifications. Although offenders are mostly versatile, there is important evidence of specialization, but much of this evidence is derived from highly technical statistical approaches. Drawing on data from a cohort of serious delinquents committed to the California Youth Authority, logistic regression models revealed robust evidence for criminal specialization net the effects of behavioral and demographic controls. Prior homicide was associated with a 1,467% increased likelihood of being currently adjudicated for a homicide offense. Similar prior-current involvement in robbery (294% increased likelihood), aggravated assault (200%), burglary (148%), and drug sales (736%) was found. Logistic regression with odds ratios provides intuitive, valuable estimates of specialization in offending whereby prior involvement in a specific form of delinquency dramatically increases the likelihood of current involvement in the same form of crime.